2015
DOI: 10.2741/4352
|View full text |Cite
|
Sign up to set email alerts
|

L-Arginine improves DNA synthesis in LPS-challenged enterocytes

Abstract: The neonatal small intestine is susceptible to damage by endotoxin, and this cytotoxicity may involve intracellular generation of reactive oxygen species (ROS), resulting in DNA damage and mitochondrial dysfunction. L-Arginine (Arg) confers a cytoprotective effect on lipopolysaccharide (LPS)-treated enterocytes through activation of the mammalian target of the rapamycin (mTOR) signaling pathway. Arg improves DNA synthesis and mitochondrial bioenergetics, which may also be responsible for beneficial effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 89 publications
(92 reference statements)
0
40
0
Order By: Relevance
“…Mitochondria are the powerhouses of the cell, producing a considerable share of cellular ATP and playing a central role in cellular function and metabolism [28]. Our previous report showed that mitochondrial dysfunction was observed with decrease in the basal respiration, maximal respiration, and nonmitochondrial respiration after LPS treatment [1]. The present data also demonstrated that mitochondrial function damage induced by H 2 O 2 was observed, showing decrease in basal respiration, proton leak, maximal respiration, spare respiratory capacity, nonmitochondrial respiration, and ATP production.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Mitochondria are the powerhouses of the cell, producing a considerable share of cellular ATP and playing a central role in cellular function and metabolism [28]. Our previous report showed that mitochondrial dysfunction was observed with decrease in the basal respiration, maximal respiration, and nonmitochondrial respiration after LPS treatment [1]. The present data also demonstrated that mitochondrial function damage induced by H 2 O 2 was observed, showing decrease in basal respiration, proton leak, maximal respiration, spare respiratory capacity, nonmitochondrial respiration, and ATP production.…”
Section: Discussionmentioning
confidence: 99%
“…DNA synthesis during cell proliferation in all treatment groups was quantified using 5-ethynyl-2′-deoxyuridine (EdU; Invitrogen) incorporation using Cell-Light EdU Kit (Rui Bo Biotechnology Limited Company, Guangzhou, China), as described in our previous studies [1]. Briefly, IPEC-J2 cells were cultured in DMEM-H mediums containing 50  μ M EdU for 1 h. An Olympus BX51 microscope (Olympus, Japan) was used to observe EdU-positive cells.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations